Using Non-Probability Sampling Methods in Agricultural and Extension Education Research - Alexa J. Lamm; Kevan W. Lamm (Journal of International Agricultural and Extension Education, 2019)
Understanding what the public thinks can guide how to target international agricultural and extension education interventions. Public opinion data can also provide insights into how the agricultural and natural resource industry communicates about emerging technologies and practices. However, the use of cellphones and the Internet have greatly reduced response rates to antiquated methods of public opinion data collection and the research world must alter its approach in response. The use of nonprobability sampling techniques has increased dramatically in public opinion research the past five years and more recently within agricultural and extension education research. To keep up with these trends, agricultural and extension education researchers must know the nuance associated with the use of nonprobability sampling techniques and how to mitigate some of the issues that may arise as a result.
Keywords: public opinion; non-probability sampling; weighting; quota sampling